Ektopien des Thymus und ektope Thymustumoren - Marx, Alexander; Rößner, Eric (Der Pathologe, 2018)
Ectopic thymic tissue outside its core position in the antero-superior mediastinum is quite common owing to the complexity of embryonal thymus development, whereby reported prevalence values (1 to 90%) are heavily dependent on the method of investigation and the intensity of the workup. The debated prevalence and relevance of ectopic thymic tissue and its accessibility underlie the ongoing discussion whether modern, minimally invasive thymectomy strategies can match the proven benefit of the radical transsternal thymectomy procedure for the treatment of Myasthenia gravis. In this context, the following article covers the etiology, prevalence, and location of normal-looking, reactive, and neoplastic ectopic thymic tissue. Furthermore, ectopic tissues and tumors inside or adjacent to the thymus are mentioned.
Englische Zusammenfassung unter dem Titel: Ectopic thymic tissue and ectopic thymic tumors
Gesehen am 14.10.2019